Ч . 2 : Введение в разведку и добычу нефти; Нефтегазовое дело. Книга для студентов - Болсуновская Л. М. Людмила Михайловна; Абрамова Р. Н. Раиса Николаевна; Матвеенко И. А. Ирина Алексеевна; Долгая Т. Ф. Татьяна Федоровна (2015, 2015)
Заглавие с титульного экрана